Serat Babad Kediri, Chronicle Of Figuration, Meaning, and Perspective: Among the Mythology, History, and Fiction - Sunoto Sunoto (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2017)
Indonesia has a wide range of the literature types. This archipelago is enriched by ancient literature that becomes the works of man in the history. Inside the Javanese literature, there is manuscript which also called as “BABAD”, this chronicle is separated depending on where each comes from, such as Babad Tanah Jawi, Serat Babad Kediri, Babad Ayat, Babad Ronggolawe, Babad Sumenep, and others. Each of that ancient manuscript, are inside the figuration, it because, those are present the three characteristics, that wraps by myth or legend, but at the same time, it was trying to represent the history of the land, and as well as enrich the Indonesian fiction literature. From a mythological perspective, figures in chronicles are beliefs or masks that are deliberately guarded and maintained by their owners. Therefore, the focus of the assessment is not to find the speaker's experience but to reveal the mask that is deliberately worn on the character. From a historical perspective, the figures in the chronicle are known to correspond to the life of the person concerned while in the primary time, or real facts. Therefore, the focus of the assessment lies in the attempt to find a correspondence between the facts mentioned therein with the fact that there is present in real life, as well as to observe from the primary interactions. Here's a fictional perspective, a chronicle is a world of fictitious life that is deliberately embodied in meaningful language. Therefore the focus of this assessment is trying to reveal the imaginative or symbolic worlds. On each of the Babad manuscript, it’s associated with the message that brings out by the messenger which embed inside the context of value and meaning. This paper focused on the Babad Kediri manuscript that written out by Mas Ngabehi Purbawijaya and published by “Boekhandel TAN KHOEN SWIE”, at the city of Kediri around 1932. It was a focus on the characterizing for the figuration inside the chronicle, from the view of myth, history, and fiction point of view.